Recent methane surges reveal heightened emissions from tropical inundated areas - Xin Lin; Shushi Peng; Philippe Ciais; Didier Hauglustaine; Xin Lan; Gang Liu; Michel Ramonet; Yi Xi; Yi Yin; Zhen Zhang; Hartmut Bösch; Philippe Bousquet; et al. (Nature Communications)
Abstract Record breaking atmospheric methane growth rates were observed in 2020 and 2021 (15.2±0.5 and 17.8±0.5 parts per billion per year), the highest since the early 1980s. Here we use an ensemble of atmospheric inversions informed by surface or satellite methane observations to infer emission changes during these two years relative to 2019. Results show global methane emissions increased by 20.3±9.9 and 24.8±3.1 teragrams per year in 2020 and 2021, dominated by heightened emissions from tropical and boreal inundated areas, aligning with rising groundwater storage and regional warming. Current process-based wetland models fail to capture the tropical emission surges revealed by atmospheric inversions, likely due to inaccurate representation of wetland extents and associated methane emissions. Our findings underscore the critical role of tropical inundated areas in the recent methane emission surges and highlight the need to integrate multiple data streams and modeling tools for better constraining tropical wetland emissions.